Pengembangan Lembar Kerja Siswa Berbasis Problem Based Learning pada Materi Bilangan Bulat Siswa Kelas VII SMP Ahmad Syarifuddin - Sukmaliya, Lilis; Itqan, Moh. Syadidul (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to develop a Problem Based Learning (PBL)-based Student Worksheet (LKS) on integer material for seventh-grade students at SMP Ahmad Syarifuddin. The development model employed was ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects involved media experts, material experts, mathematics teachers, and seventh-grade students. The research instruments included interview guidelines, validation questionnaires, and student response questionnaires. The validation results indicated that assessments from media experts obtained a percentage of 77% (categorized as highly feasible), while material experts provided a percentage of 87% (categorized as highly feasible). In addition, the limited trial with students yielded a positive response of 75% (categorized as valid). These findings suggest that the developed PBL-based LKS is valid, practical, and effective to be utilized as a mathematics learning medium on integer material, as well as having the potential to enhance students’ engagement and understanding.